2011
DOI: 10.1186/1477-7819-9-64
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3D-computed tomography angiography for planning the surgical removal of pineal region meningiomas using Poppen's approach: a report of ten cases and a literature review

Abstract: BackgroundThere are several treatment approaches for pineal region meningiomas, such as Poppen's approach, Krause's approach and combinations of the two approaches. We present our experience with the use of 3D-computed tomography angiography for planning the surgical removal of pineal region meningiomas using a suboccipital transtentorial approach (Poppen's approach) and evaluate the role of Poppen's approach.MethodsDuring the period from January 2005 to June 2010, ten patients presented to us with pineal regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The role of melatonin in aging and Alzheimer's disease suggested by Wu YH et al 16 , the association of amount of brain sand and schizophrenia shown by Savel'ev et al 17 , the importance of pineal gland anatomy in the surgical management of pineal tumors 18 , all these signify the importance of updating data on pineal gland anatomy. In order to correlate the morphological and microscopic features of pineal gland with its secretory activity and physiological significance, investigations in the form of serum estimation of melatonin and immunohistochemical studies of enzymes in the pinealocytes are needed which could not be included in this work.…”
Section: Discussionmentioning
confidence: 98%
“…The role of melatonin in aging and Alzheimer's disease suggested by Wu YH et al 16 , the association of amount of brain sand and schizophrenia shown by Savel'ev et al 17 , the importance of pineal gland anatomy in the surgical management of pineal tumors 18 , all these signify the importance of updating data on pineal gland anatomy. In order to correlate the morphological and microscopic features of pineal gland with its secretory activity and physiological significance, investigations in the form of serum estimation of melatonin and immunohistochemical studies of enzymes in the pinealocytes are needed which could not be included in this work.…”
Section: Discussionmentioning
confidence: 98%
“…2,11 However, most pineal region meningiomas grow downward from the origin and are located below the falcotentorial junction, and they displace the galenic venous system downward. 10 Pineal region meningiomas, which originate near the falcotentorial junction, receive blood supply from the meningeal arteries along the tentorium and falx, and tend to grow in both infra-and supratentorial spaces with lateral extension.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, the OTA is preferable in most cases, because of the access to the pineal region without sacrificing the bridging veins from the cerebellar tentorial surface, early devascularization of the feeding arteries along the tentorium and falx, and exposure of both the supra-and infratentorial spaces. 2,9,10,15,16 However, pineal region meningiomas, especially large ones, tend to be separated into 4 anatomical compartments by the cerebral falx, bilateral tentorium, and cerebellar falx. Furthermore, the straight sinus is located in the junction between the falx and tentorium and receives venous blood from the bilateral internal cerebral veins, vein of Galen, bilateral basal veins, and internal occipital veins.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, the images available from 3D-CTA have been useful for the sophisticated preoperative planning of the meningioma. 3D-CTA clearly shows the relationship between vessels and the tumor, and also enables the vessels to be protected from damage during surgery (17). …”
Section: Discussionmentioning
confidence: 99%